2016
DOI: 10.1097/mao.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Postoperative Follow-up Diffusion-weighted Magnetic Resonance Imaging to Detect Residual or Recurrent Cholesteatoma

Abstract: Despite cholesteatoma surgery without macroscopic residue, clinical follow-up and routine first follow-up DWI without any signs of residual or recurrent disease, repeat follow-up DWI showed evidence of cholesteatoma in 31% of patients. On the basis of the findings in this study, repeated follow-up DWI is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
4
21
1
Order By: Relevance
“…We found acquisition times between 3 and 6 minutes for 1 b-value with non-EPI-DWI in the literature, 21 and some studies did not indicate the acquisition time. 12,[24][25][26] Therefore, comparison between different sequences is always difficult. As with sequences used in other studies, many parameters such as slice thickness, number of slices, and FOV must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…We found acquisition times between 3 and 6 minutes for 1 b-value with non-EPI-DWI in the literature, 21 and some studies did not indicate the acquisition time. 12,[24][25][26] Therefore, comparison between different sequences is always difficult. As with sequences used in other studies, many parameters such as slice thickness, number of slices, and FOV must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…If available, coloured image-fusion of DWI and anatomic sequences helps to better demonstrate the findings to patients or clinicians. On the basis of the findings by Steens et al[34] repeated follow-up DWI after surgery of cholesteatoma is recommended. Their study showed an evidence of cholesteatoma in 31% of the patients on repeated follow-up DWI.…”
Section: Dwi For the Daily Clinical Practisementioning
confidence: 99%
“…6 ). A recent study demonstrated that in patients with a negative first post-operative follow-up DWI and no clinical signs of post-operative cholesteatoma, a repeat second-follow up scan (performed at least 6 months after first follow-up DWI) was positive or equivocal for disease in 14 out of 45 (31 %) ears, with five ears having cholesteatoma confirmed on surgical exploration [ 40 ]. In addition, 2 third-follow-up DWI scans, which were previously negative, turned positive for cholesteatoma and was confirmed on surgery.…”
Section: Navigating Past the Pitfalls In Sensitivitymentioning
confidence: 99%